Removal of Linear Alkyl Benzenesulphonate by Quaternized Rice Husk - Low, K. S.; Lee, C. K.; Cheong, C. K. (Universiti Putra Malaysia Press, 1998)
The potential for the use of quaternized rice husk as a sorbent for the removal of linear alkyl benzenesulphonate from aqueous solution was investigated. Both batch and column studies were carried out. The results of the batch studies indicate that sorption was pH dependent, with maximum sorption being attained at pH 2.2. The removal of linear alkyl increased as the temperature increased from 4 to 50°C; thereafter uptake remained constant with further increase in temperature. The presence of anions such as CI', Hl04 ', HPO/ and SO/, had little effect on sorption. Experimental data could be fitted into the Langmuir isotherm with a maximum sorption capacity of 243.9 mg/g at pH 2.2 and 28 ± 2C. In the column studies, results show that a linear relationship existed between service time and bed-depth. However, flow rate of influent had no effect on breakthrough time once it was above 10 ml/min.